Efektivitas Pembayaran Pajak Kenderaan Bermotor pada Kantor Samsat Kabupaten Pakpak Bharat - Dienti Frelli Marbun; Andi Nova Bukit (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2024)
One source of development financing is obtained from fiscal policy, namely the use of taxes with the aim of promoting economic development. As one source of development financing, Motor Vehicle Tax is certainly worth researching how effective its collection is. Motor Vehicle Tax is a potential for tax revenue where the number of vehicles each year in the District. Pakpak Bharat continues to improve. The results obtained within the research time span were 1) the target of the motor vehicle tax in the district. Pakpak Bharat increases in line with the increasing number of motorized vehicles. 2) For the effectiveness of Motor Vehicle Tax in 2012-2013 revenue was effective and for 8 consecutive years (2014-2021) Motor Vehicle Tax revenue was very effective but decreased in 2022 revenue was again in the effective category 3) the existence of E Samsat made It is easier for the public to know and pay motor vehicle tax and 4) there are still many motor vehicle taxes owed due to the public's lack of awareness about paying their vehicle tax.